Healthy at home for COPD: an integrated digital monitoring, treatment, and pulmonary rehabilitation intervention - Laurel O’Connor; Stephanie Behar; Seanan Tarrant; Pamela Stamegna; Caitlin Pretz; Biqi Wang; Brandon Savage; Thomas Scornavacca; Jeanne Shirshac; Tracey Wilkie; Michael Hyder; Adrian Zai; et al. (BMC Digital Health)
Abstract Background Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality in the United States. Frequent exacerbations result in higher use of emergency services and hospitalizations, leading to poor patient outcomes and high costs. The objective of this study is to demonstrate the feasibility of a multimodal, community-based intervention in treating acute COPD exacerbations. Results Over 18 months, 1,333 patients were approached and 100 (7.5%) were enrolled (mean age 66, 52% female). Ninety-six participants (96%) remained in the study for the full enrollment period. Fifty-five (55%) participated in tele-pulmonary-rehabilitation. Participants wore the smartwatch for a median of 114 days (IQR 30–210) and 18.9 h/day (IQR16-20) resulting in a median of 1034 min/day (IQR 939–1133). The rate at which participants completed scheduled survey instruments ranged from 78–93%. Nearly all participants (85%) performed COPD ecological momentary assessment at least once with a median of 4.85 recordings during study participation. On average, a 2.48-point improvement (p = 0.03) in COPD Assessment Test Score was observed from baseline to study completion. The adherence and symptom improvement metrics were not associated with baseline patient activation measures. Conclusions A multimodal intervention combining preventative care, symptom and biometric monitoring, and MIH services was feasible in adults living with COPD. Participants demonstrated high protocol fidelity and engagement and reported improved quality of life. Trial Registration The study is registered at Clinicaltrials.gov NCT06000696 (Registered on 08/14/2023).